A global nursing framework in the Swedish Red Cross undergraduate nursing program. (September 2018) - Holmgren, Jessica; Kraft, Mia
Alongside a globalized world and a demographic shift in Sweden, future nurses must provide globally significant nursing care based on relevant knowledges and skills. To contribute to the global nursing discourse, this article aims to describe the process undertaken in developing and implementing a global nursing approach and curriculum in the Swedish Red Cross undergraduate nursing program. A comprehensive process of educational change was carried out, targeting both faculty and students with various academic activities. The new global-oriented curriculum was evaluated positively by nursing students, and a definition of global nursing was disseminated among educators. Nursing students at the Swedish Red Cross University College are now encouraged to advocate for vulnerable persons in need of healthcare services and to counteract inequalities and social injustice in sustainable ways. It is suggested that a global nursing framework is what is required when educating nurses to meet tomorrow's nursing care needs.